1977
DOI: 10.1042/cs0520043
|View full text |Cite
|
Sign up to set email alerts
|

Increased Renal Function in Patients with Acute Left Ventricular Failure: A Possible Homeostatic Mechanism

Abstract: 1.Creatinine clearance and urine excretion have been measured in fifty-five patients admitted with suspected myocardial infarction. Patients were grouped on the basis of their radiological report on the first day, irrespective of their diagnosis. The first group consisted of twenty-six patients with normal chest X-rays, the second group of twenty-two patients with radiological evidence of upper zone vessel dilatation and the third group of seven patients with radiological evidence of pulmonary oedema, who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Thus, it has been shown that other vascular beds behave differently from skeletal muscle during myocardial ischemia than has been previously observed for skeletal muscle beds (5,11). In this regard, it has recently been reported that patients with acute myocardial infarction and evidence of elevated left-sided filling pressures have higher creatinine clearance, urine volume, atid sodium excretion than do patients with myocardial infarction and normal filling pressures (12). It is possible that this acute elevation of cardiac filling pressu're may have activated sensory endings in the left atrium and left ventricle.…”
Section: Introductionmentioning
confidence: 82%
“…Thus, it has been shown that other vascular beds behave differently from skeletal muscle during myocardial ischemia than has been previously observed for skeletal muscle beds (5,11). In this regard, it has recently been reported that patients with acute myocardial infarction and evidence of elevated left-sided filling pressures have higher creatinine clearance, urine volume, atid sodium excretion than do patients with myocardial infarction and normal filling pressures (12). It is possible that this acute elevation of cardiac filling pressu're may have activated sensory endings in the left atrium and left ventricle.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, hemorrhagic shock induces a marked vasoconstriction in the kidney (Gorfinkel et al, 1972), and the vasoconstriction contributes to the development of acute renal failure. Studies by Bennet et al (1977Bennet et al ( , 1978 are also of great interest in this respect. These authors examined the renal function in patients with acute myocardial infarction and moderate left ventricular failure as showed by radiologic measurement of the heart size.…”
Section: Vagal Depressor Reflexes and Arrhythmias In The Earlymentioning
confidence: 97%
“…Interestingly enough, patients with myocardial infarction and acute congestive heart failure show increased urine flow and glomerular filtration rate despite the fall in arterial blood pressure (Efendigil et al, 1975;Bennet et al, 1977). Several of these patients also showed an increased sodium output (Bennet et al, 1978).…”
Section: Cardiac Receptors In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In man, Bennett et al (1977) have shown that there is an unexpected diuresis in the acute and early stage of left ventricular failure after myocardial infarction, but this does not persist. It might, therefore, be argued that in patients with angina who do not show a chronic rise in enddiastolic pressure or an enlarged heart, the constant short-lasting acute pressure rises associated with angina might lead to diuresis and hence to a reduction in blood volume (Sleight and Widdicombe, 1965).…”
Section: Discussionmentioning
confidence: 99%